Enteric fever in endemic areas of Indonesia: an increasing problem of resistance - Mochammad Hatta; Name Ratnawati (Journal of Infection in Developing Countries)
Reported levels of antibiotic resistance in Salmonella Typhi from South Sulawesi, Indonesia were very low (< 1%) before 2001 and chloramphenicol remained the treatment of choice. Since 2001 however resistance has been rising and in 2007 6.8% of isolates were resistant to all three first line drugs: Ampicillin, chloramphenicol and co-trimoxazole. Ciprofloxacin resistance is currently at 3.90 %. At the same time there has been an increase in the number of reported cases. This may be because of improved diagnostics or it may be a genuine outbreak of drug resistant S. Typhi. In conclusion drug resistant typhoid fever will become a serious problem in Indonesia in the future, requiring the use of expensive drugs for the treatment of typhoid. A concerted effort is needed by the medical services to implement reliable diagnosis so that treatment or vaccination can be used to control the spread of drug resistant typhoid fever.